2019
DOI: 10.1016/j.molmet.2019.08.020
|View full text |Cite|
|
Sign up to set email alerts
|

Fibroblast growth factor 21 is required for the therapeutic effects of Lactobacillus rhamnosus GG against fructose-induced fatty liver in mice

Abstract: ObjectivesHigh fructose feeding changes fibroblast growth factor 21 (FGF21) regulation. Lactobacillus rhamnosus GG (LGG) supplementation reduces fructose-induced non-alcoholic fatty liver disease (NAFLD). The aim of this study was to determine the role of FGF21 and underlying mechanisms in the protective effects of LGG.MethodsFGF21 knockout (KO) mice and C57BL/6 wild type (WT) mice were fed 30% fructose for 12 weeks. LGG was administered to the mice in the last 4 weeks during fructose feeding. FGF21-adiponecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 76 publications
(95 reference statements)
3
34
0
Order By: Relevance
“…[ 6,10 ] Furthermore, numerous studies show that adipokines are required for some therapeutic agents to perform their anti‐NAFLD functions in rodent models. [ 11–14 ] Therefore, regulation of adipokine secretion may serve as a potential therapeutic strategy for NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,10 ] Furthermore, numerous studies show that adipokines are required for some therapeutic agents to perform their anti‐NAFLD functions in rodent models. [ 11–14 ] Therefore, regulation of adipokine secretion may serve as a potential therapeutic strategy for NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD—one of the most prevalent liver diseases in adults—is characterized by an irregular accumulation of triglycerides in hepatocytes [ 1 , 22 ]. Recent studies have reported the administration of probiotics such as Lactobacillus for the treatment and prevention of NAFLD in animal models [ 9 , 23 ]. B. uniformis which is dominant in the human gut, showed anti-obesity effects in mice with HFD-induced obesity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that FGF-21 may have a protective role in energy metabolism by acting as an insulin sensitizer [29] and by stimulating the oxidation of fatty acids and inhibition of lipogenesis [30]. Furthermore, FGF-21 was shown to protect against fructose-induced liver inflammation in mice [31]. Nevertheless, elevated circulating FGF-21 levels have been associated with poor metabolic health in humans and shown to correlate positively with fasting glucose [32], fasting insulin, and triglycerides and negatively with high-density lipoprotein cholesterol (HDL) [33].…”
Section: Discussionmentioning
confidence: 99%